2011
DOI: 10.1002/anie.201005624
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Complexes of a Dicyclometalated Phosphite Tripod Ligand: Strategy to Achieve Blue Phosphorescence Without Fluorine Substituents and Fabrication of OLEDs

Abstract: Organic light-emitting diodes (OLEDs) based on heavy transition-metal complexes are playing a pivotal role in next generation of, for example, flat panel displays and solid-state lighting.[1] The readily available, Os II -, Pt II -, and in particular Ir III -based phosphorescence complexes grant superior advantage over fluorescent materials.[2] This is mainly due to heavyatom-induced spin-orbit coupling, giving effective harvesting of both singlet and triplet excitons. However, tuning of phosphorescence over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Arylpyridine‐type blue triplet emitters have electron‐deficient aryl units as the HOMO determining unit and a pyridine‐derived unit as the LUMO determining unit to widen the HOMO‐LUMO gap of emitters for blue emission. Examples of electron‐deficient aryl units are F‐substituted phenyl, CN‐substituted phenyl, CF 3 ‐substituted phenyl and pyridinyl moieties . The electron‐deficient aryl units deepen the HOMO level of the triplet emitters and shift the emission spectrum to a blue emission wavelength.…”
Section: Phosphorescent Emittersmentioning
confidence: 99%
“…Arylpyridine‐type blue triplet emitters have electron‐deficient aryl units as the HOMO determining unit and a pyridine‐derived unit as the LUMO determining unit to widen the HOMO‐LUMO gap of emitters for blue emission. Examples of electron‐deficient aryl units are F‐substituted phenyl, CN‐substituted phenyl, CF 3 ‐substituted phenyl and pyridinyl moieties . The electron‐deficient aryl units deepen the HOMO level of the triplet emitters and shift the emission spectrum to a blue emission wavelength.…”
Section: Phosphorescent Emittersmentioning
confidence: 99%
“…Hence, a large 3 MLCT contribution will increase the quantum yield ( Φ PL ). We calculated MLCT% of all the derivatives under study following chou's work, as shown in Table . It can be seen that 3 MLCT% is affected by the different substituents and their grafted positions.…”
Section: Resultsmentioning
confidence: 99%
“…Deep blue emissions were observed in the OLEDs fabricated from 24c showed a peak PE of 8.6 lm W −1 (CIE = 0.16, 0.11). In a later report, the efficiency was improved by the use of a phosphite tripod P ^ C ^ C type ligand in complexes 25a–c . It was suggested that the tripod ligand could enhance the long term stability of the complex in device operation.…”
Section: Phosphorescent Transition Metal Complexesmentioning
confidence: 99%